The influence of social category cues on the happy categorisation advantage depends on expression valence - Craig, B.; Koch, S.; Lipp, Ottmar (Routledge, 2016)
Facial race and sex cues can influence the magnitude of the happy categorisation advantage. It has been proposed that implicit race or sex based evaluations drive this influence. Within this account a uniform influence of social category cues on the happy categorisation advantage should be observed for all negative expressions. Support has been shown with angry and sad expressions but evidence to the contrary has been found for fearful expressions. To determine the generality of the evaluative congruence account, participants categorised happiness with either sadness, fear, or surprise displayed on White male as well as White female, Black male, or Black female faces across three experiments. Faster categorisation of happy than negative expressions was observed for female faces when presented among White male faces, and for White male faces when presented among Black male faces. These results support the evaluative congruence account when both positive and negative expressions are presented.